Neurological injury monitoring using qeeg - Rasheed, W. (CRC Press, 2014)
The human brain is the most resilient and pliable structure in the human body as well as in nature. The brain is the source of human emotions, perceptions, thoughts, memories, and behaviors that collectively define a personality. The brain comprises hundreds of billions of neurons or nerve cells. These microscopic elements employ a chemical messaging mechanism to regulate electrical activity throughout the brain. These activities define emotions, perceptions, and thoughts. However, the intricate mechanism of how a brain forms as a mind has not been understood as yet. It must also be noted that after developed inside the motherâs womb, nerve cells cannot recover from any forms of injury, but just degenerate. Â© 2015 by Taylor & Francis Group, LLC.